A STUDY OF DEMOGRAPHIC PROFILE IN FATAL ROAD TRAFFIC ACCIDENT INDORE REGION OF MADHYA PRADESH - Soni, Sunil Kumar; Thakur, P S; Singh, Bajrang K; Tomar, J S; Dadu, S K. (Journal of Forensic Medicine and Toxicology, 2021)
Background: Head injuries are the most serious injuries in the term of morbidity and mortality. This study was conducted in M.G.M. Medical College, Indore, mortuary among the 200 post mortem cases of road traffic accident victims over the period of one year from 1st October 2014 to 30th September 2015. Objective: To find out demographic profile in fatal road traffic accident victims. Results: In Males most common age group affected was 21-30 years (32.5%) followed by 31-40 years (19.0%). Equal incidence in Female between age group 21-30 years and 31-40 years; (25.0%). Males (78.0%) outnumbered the Females (22.0%) with male and female ratio as 3.5:1 in victims of all head injury cases in RTA. Most of the victims were literate (80.50%). Accidents were common in urban area (71.0%) as compared to rural area (29.0%). More than 90% incidences occurred between 8:01pm - 12:00am. Accidents were most common in rainy season (70.0%). Most involved vehicle was two wheeler (83.0%). Among the victims riders (46.5%) were maximum and pedestrians (15.5%) were minimum. Most of two wheelers victims (n=159; 95.79%) were not wearing helmet. City road were more common site for fatal accidents (50.5%).